Carabid activity‐density increases with forest vegetation diversity at different spatial scales. Issue 1 (14th August 2019) - Jouveau, Séverin; Toïgo, Maude; Giffard, Brice; Castagneyrol, Bastien; van Halder, Inge; Vétillard, Fabrice; Jactel, Hervé
Abstract: More diverse forests are generally more resistant to insect herbivores. This might be due to positive effects of tree diversity on predation. Although the enemies hypothesis has received conflicting evidence in forest ecosystems. Carabids were sampled by pitfall trapping in a tree diversity experiment, at the centre of plots ranging from one to five tree species mixtures. The composition and vertical structure of the vegetation was assessed at three scales, in the understorey, in the canopy of the experimental plots, and in the surrounding area of each plot. None of the tested vegetation variables had an effect on the species richness of carabids. In contrast, the vegetation compositional diversity at the understorey, canopy and surrounding scales had additive and positive effects on the activity‐density of the carabids. Our findings indicate that more diverse forests can host a higher activity‐density of predatory carabids, as a result of the combined effect of horizontal and vertical vegetation diversity, which might increase both habitat quality and the amount of feeding resources. This highlights the relevance of manipulative tree diversity experiments to identify the ecological filters shaping local carabid communities. Abstract : Close‐up on the aerial photograph of one block of the ORPHEE experiment, where carabids were pitfall trapped at the centre of all 32 plots, ranging from one to five species mixtures. The diversity of vegetation in the understorey, canopy and surrounding areas of the plots had additive and positive effects on the activity‐density of carabids. Likely reasons are the improvement of habitat quality and the amount of food resources for predatory and omnivorous carabids.